What does Psychological Well-being Mean for Mexican Late Adolescents? A Study with Natural Semantic Networks in the Post-pandemic Era - César A. García-Avitia; Sara L. Pérez-Ruvalcaba; Claudia V. Márquez-González (Psychology in Russia: State of Art)
Background. Well-being is distinguished by its complex and multifaceted characteristics, integrating both objective and subjective components, so each person's point of view is relevant. In conducting research concerning well-being, it is important account for both age considerations and cultural variability. Additionally, the influence the COVID-19 pandemic should be considered given how it impacted the public including corresponding effects on peoples’ perceptions of well-being. Objective. The study’s purpose was to analyze the meaning of psychological well-being from the perspective of late adolescents presiding in Colima, Mexico during the post-pandemic era. Design. A non-experimental, cross-sectional and exploratory research design was used. The Natural Semantic Networks technique was used as the instrument of measurement, employing psychological well-being as the stimulus concept to study a sample of 112 high school students in late adolescence (92 women, 20 men, ages 17 to 21; average = 17.3). The Natural Semantic Networks research technique enabled the exploration of participants' subjective meanings associated with well-being. Results. The analysis identified a set of primary categories of well-being defined by participants including: health, both physical and mental; low-arousal emotions, such as peace and serenity; positive affect like happiness; positive relationships, mainly with family; security; self-control; and self-acceptance. Conclusion. This research highlights that no single theory fully captures adolescents' understanding of well-being. Crucial elements considered by the most important theories are missing from participants conceptual frameworks. Additionally, COVID-19 pandemic has affected adolescent perceptions of well-being, especially it its impact on mental health. Peace is also valued as relevant by participants, especially desirable in the midst of emotional turbulence. Results show the need for a more comprehensive perspective on well-being that incorporates specific dimensions of each age group within a cultural and temporal context.